Pengaruh Health Education Triase Terhadap Tingkat Kecemasan Keluarga Di Instalasi Gawat Darurat Rsu Mayjen H.A Thalib Kota Sungai Penuh Tahun 2025 - Moza Suzana; Thrisia Monica (Universitas Sumatera Barat, 2025)
In Indonesia, data on family visits experiencing anxiety to the Emergency Room in 2023 showed that families experiencing anxiety amounted to 16,712,000 (28.2% of total visits). The purpose of this study was to determine the effect of triage health education on the level of family anxiety in the Emergency Room. This study employs a quantitative approach with a Pre-Experimental research design, specifically a one-group pre-test-post-test design. The sampling technique used was the Random Sampling technique. The population in this study was all patients who visited the Emergency Room in 2024, amounting to 14,561 people, with a sample of 16 people. This study was conducted at the Emergency Room of Mayjen H. A Thalib General Hospital, Sungai Penuh City, from January to June 2025. The instrument used to measure anxiety was the Anxiety Level Self-Assessment. The average result was obtained for all 16 (100.0%) respondents with an anxious family anxiety level before being given triage health education. Meanwhile, the average of all 16 (100.0%) respondents with a family anxiety level was not anxious after being given triage health education, with a p-value = 0.000 (p ≤ 0.05). The conclusion of the study shows that there is an effect of triage health education on the level of family anxiety in the Emergency Department. The researcher's suggestion from the results of the study is that it can be applied to health workers in providing green and yellow triage health education, so that families will no longer be anxious when taking their families to the hospital.